Implications of social isolation for children due to the new coronavirus (COVID-19) - Alvarenga, Beatriz Crivelli; Colpas, Andrea Pereira; Dantas, Bruna Azevedo; Damasceno , Cecília Cândida Graça Mota; Brito , Gabriela Machado; de Almeida , Fernanda Rodrigues; Decnop, Letícia Barroso Mangelli; Goifman, Luna Rocha; da Silva, Isabella Martins; Fiorot, Paula Amaral Silva Perini; Skitnevsky, Suzana Carvalho (Seven Editora, 2023)
Social isolation, due to the COVID-19 pandemic, is a situation of adversity in the development of the child. Social withdrawal, deprivation of interacting with other people and changes in habits significantly increase children's daily stress. As a consequence of such measures, stress, anxiety, depression, emotional overload and worsening mental health have affected, especially children, as they still do not have the cognitive tools necessary to deal with this new reality. The objective of this work is to identify and discuss the implications of social isolation for children in times of a pandemic, in order to present its difficulties, consequences and recommendations. The present study consists of a systematic literature review, carried out from the selection of articles. The databases were taken from selected scientific articles from 2009 to 2020 through a search in the Scielo database. The bibliographic search was carried out using the following descriptors: child, isolation, covid-19 and coronavirus.When considering the pandemic as a prolonged stressful event and with a measure of social distancing, it is relevant to note that the current situation has no precedent with similar characteristics. In this sense, it is still difficult to assess the psychological impacts and how much the development of children will be affected. In view of the current scenario, it is a fundamental role of those responsible to make the environment less stressful for children and to carry out conversations about the situation with language and an appropriate approach for the child's age.DOI:https://doi.org/10.56238/emerrelcovid19-028